TRENDS OF UNDERSTANDING OF NATURE IN MODERN SOCIETY - Ramadan Shah Putra; Ira Suryani (Universitas Dharmawangsa, 2021)
This paper discusses the understanding of morality, which can change over time and the passage of time. The Islamic treatise brought by the Prophet Muhammad focused on perfecting human morals. Humans as managers of the universe are given the authority to utilize all their physical and spiritual abilities, reason and mind in order to provide human welfare. Human welfare provides an opportunity for him to be able to be better in terms of science, technology and human civilization itself. For this reason, the management of the universe must be supported by human taste, intention and reason. Science and technology have made human life easier. Modern humans are characterized by the rapid development of science and technology. Technology makes significant changes, thereby changing human lifestyles. Likewise with morality. The morality of modern society is influenced by the understanding it gets from family, educational institutions, the environment, society and the media. The rapid development of science and technology has made human life easier. Human life that is getting easier causes changes in patterns of thought and action which in turn shifts the morals of the human personality.